Flow analysis using RDDA method with actual usage in water distribution network - Lee, Hyundong; Choi, Si-Hwan (International Journal of Engineering and Technology, 2018)
In the analysis of the water pipeline network, the amount of demand applied is assumed based on the valve being open 24 hours, unlike cases where water is supplied when the valve is opened and blocked when it is closed. As a result, existing analysis results and actual survey data show a lot of differences in hydraulic pressure and flow rate. Also, problems such as faulty outflow, lack of pumping capacity, low reservoir height, and failure to operate decompression facilities have been confirmed. In this paper, a real demand driven analysis method is proposed to solve these problems. First, a virtual flow control facility, a virtual low water column, and a virtual node are applied to the analytical model. In the next step, as the existing demand amount is used at the virtual node, if the water in the reservoir is below a certain level water is supplied from the flow control facility and the flow is shut off when the water level exceeds a certain level. This is a method to analyze the water pipeline network by supplying the usage amount.Â